Utilization of bulbous plants in landscape architecture growing in Lakes Region - Naşit KILIÇASLAN; Şirin DÖNMEZ (Turkish Journal of Forestry, 2016)
In this study, aimed to determine, the bulbous plants growing naturally in the Lake district, the possibilities of use in landscape architecture. In this context, it was found 191 bulbous plants identified in the floristic studies that has been done in the Lake district. These plants have been evaluated due to their utilization at landscape architecture (it is or not endemic, ornamental flowers, fragrance, medicinal and aromatic use, shade and resistance to semi-shade, use the flower beds, soil tolerance is high, median-use, natural and artificial water's edge use, exhibition and demonstration purposes, the rock for use in the garden). Consequently it was determined 107 plant species which 31 of them are endemic heaving 5 or more properties. Creating a flowering calendar of those plants that the opportunity remain flowers all year round for bulbous plants in use in the planting design applications were put forward.